If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
5*x-(4*((-3/2)*x+2)) = y // - y
5*x-(4*((-3/2)*x+2))-y = 0
5*x-4*((-3/2)*x+2)-y = 0
5*x-4*(2-3/2*x)-y = 0
5*x-4*(2-3/2*x)-y = 0
11*x-y-8 = 0
11*x-y-8 = 0
11*x-y-8 = 0 // + -y-8
11*x = -(-y-8) // : 11
x = (-(-y-8))/11
x = (y+8)/11
x = (y+8)/11
| 5x-5=12-68 | | f(x)=2x(4)-3x+4 | | 4x+13=8x+25 | | -x+42=4x | | -2.5+g=-1.3-1.1 | | (3x+4)(5x+9)= | | 36=8-7y | | 0.5x+1.2=0.8x-1.2 | | .75x=36.75 | | 9x+14=5x+2 | | x/3+x/6=5 | | g=7*1/2 | | 13(x+6)-3=3+-5 | | -0.10(33)+0.85x=0.05(x-2) | | f--40=-12 | | .15x=5.25 | | 3(8+2x)(5+2x)=(14.5+2x)(15+2x) | | x^2-7x+12.25=.25 | | 3(n+2)=6-3(n+4) | | 4(20-2n)=4 | | 6x^2=3x+30 | | x-4/3+4/3=-x/2 | | 61/4-32/3 | | 2/7x=2 | | 497-x/3 | | 2(x-3)/5=12 | | e--36=-5 | | x=5+1 | | 5(n+2)+10=20 | | (6x^3-3x^2+4x)-(4x^2+3x+8)= | | 2x/3+20=30 | | 3(x-2)-x=12+5x |